Economics and the global environment - Pearson, Charles S (Cambridge Cambrdige University Press, 2000)
Economics and the global environment is a comprehensive analysis of how economic and environmental economic systems mesh in the international context.This book investigates how envirmental resources such as global climate,genetic diversity.This book will
Keywords: Environmental economics; Sustainable development; Environmental policy-International cooperation